The role of variants regulating metformin transport and action in women with polycystic ovary syndrome. (November 2016) - Pau, Cindy T; Cheang, Kai I; Modi, Bhavi P; Kasippillai, Thushiga; Keefe, Candace C; Shulleeta, Maria; Evans, William S; Pal, Lubna; Strauss, Jerome F; Nestler, John E; Welt, Corrine K
Aims: Variants in genes encoding metformin transport proteins and the ATM gene are associated with metformin response. We hypothesized that these gene variants contribute to variable metformin treatment response in polycystic ovary syndrome.Materials & methods: The discovery cohort (n = 38) was studied in an open-label study. Results were replicated in two additional cohorts (n = 26 and n = 131). Response was assessed after 3–6 months of treatment with metformin extended-release 1500–2000 mg/day.Results: The rs683369 variant was associated with less weight loss in the discovery cohort (p = 0.003), but these results were not replicated (p = 0.8). There were no differences in glucose parameters, testosterone levels or ovulatory frequency as a function of genotype.Conclusion: Variants in organic ion transporters do not explain the variable metformin response in polycystic ovary syndrome.